Diagnóstico ambiental das águas do estuário Jundiaí-Potengi pela determinação dos índices de qualidade da água e toxidez - Costa, Emily Cíntia Tossi de Araújo (2008)
This study is an environmental diagnosis of the Jundiaí-Potengi/RN estuarine system waters, using calculations of pollution indicator indices such as the Water Quality Index (WQI) and the Toxicity Index (TI). The samples were collected at twelve points on the estuary, at high and low tide, between August and November 2007, over four campaigns. The study area, located in a high impact region, has various activities on its banks such as: discharge of untreated or undertreated domestic and industrial sewage, shrimp farming, immunizer stabilization lakes, riverside communities, etc. All the parameters analyzed were compared to the limits of CONAMA Resolution No. 357 of 2005 for healthy and saline Class 1 waters. The results found prove the impact caused by various activities, mainly the parameters related to the presence of organic material, such as DQO, DBO, COT and thermotolerant colliforms. The IQA for most of the collection points was of medium quality. For the metals, although values above the Resolution limits were found, most of them were lower than the detection limits of ICP-OES used, indicating that they tend to be transported by the dynamic of the tides or rainfall and are deposited in bottom sediments, resulting in a TI of 1.0 in this water, when they are absent, which occurs in most cases, or 0.0, when heavy metals are found in these waters